Utility of N-Bromosuccinimide–Water Combination as a Green Reagent for Synthesis of N,S-Heterocycles and Dithiocarbamates from Styrenes - Matloubi Moghaddam, Firouz; Goudarzi, Mehri (Synlett, 2020)
An efficient and unprecedented green protocol has been developed for the synthesis of N,S-heterocycles from styrenes and alkyl dithiocarbamates with high to excellent yields. The reaction of primary or secondary amines, CS2, and styrenes was carried out in water in the presence of a catalytic amount of an inorganic base. All products were made by using an N-bromosuccinimide–H2O combination as a green and inexpensive reagent.
Keywords: dithiocarbamates; styrenes; green chemistry; thiazoles; bromosuccinimide